PROSPECT: A comprehensive sample acquisition and analysis package for lunar science and exploration - Trautner, R.; Barber, S. J.; Fisackerly, R.; Heather, D.; Houdou, B.; Howe, C.; Iacobellis, S.; Leese, M.; Mariani, A.; Meogrossi, G.; Murray, N.; Panza, C.; et al. (Frontiers in Space Technologies, 2024)
PROSPECT is a comprehensive payload package developed by the European Space Agency which will support the extraction and analysis of lunar surface and subsurface samples as well as the acquisition of data from additional environmental sensors. The key elements of PROSPECT are the ProSEED drill and the ProSPA analytical laboratory. ProSEED will support the acquisition of cryogenic samples from depths up to 1m and deliver them to the ProSPA instrument. ProSPA will receive and seal samples in miniaturized ovens, heat them, physically and chemically process the released volatiles, and analyze the obtained constituents via mass spectrometry using two types of spectrometers. Contextual information will be provided by cameras which will generate multispectral images of the drill working area and of acquired samples, and via temperature sensors and a permittivity sensor that are integrated in the drill rod. The package is designed for minimizing volatile loss from the sample between acquisition and analysis. Initially developed for a flight on the Russian Luna-27 mission, the payload package design was adapted for a more generic lander accommodation and will be flown on a lunar polar lander mission developed within the NASA Commercial Lunar Payload Services (CLPS) program. PROSPECT targets science and exploration in lunar areas that might harbor deposits of volatiles, and also supports the demonstration of In-Situ Resource Utilization (ISRU) techniques in the lunar environment. PROSPECT operations are designed to be automated to a significant degree but rely on operator monitoring during critical phases. Here, we report the PROSPECT flight design that will be built, tested, and qualified according to European space technology engineering standards before delivery to the lander provider for spacecraft integration. The package is currently in the hardware manufacturing and integration phase with a target delivery to the NASA-selected CLPS lander provider in 2025.